Pengaruh Brand Image, Kualitas, Layanan Dan Digitalisasi Terhadap Loyalitas Nasabah Bank Bengkulu - Jepri Apizal; Lakoni, Idham; Puspita, Veny (Jurnal Adminitrasi Bisnis Nusantara, 2025)
This study aims to determine the Influence of Brand Image, Quality, Service and Digitalization on Customer Loyalty of Bank Bengkulu. The research sample in this study amounted to 105. The sampling technique is purposive sampling. The data used in this study is primary data. The analysis method of this study is a quantitative method using multiple linear regression analysis tools, multiple correlations, coefficient of determination, t-test and f-test which are processed using IBM SPSS software version 27. The results of the study indicate that the independent variables Brand Image, Service Quality and Digitalization simultaneously have a positive and significant influence on the dependent variable Customer Loyalty of Bank Bengkulu, the Brand Image variable partially has a positive and significant influence on the Customer Loyalty variable. The Service Quality variable partially has a positive and significant influence on the Customer Loyalty variable, and the Digitalization variable partially has a positive and significant influence on the Customer Loyalty variable.